The Function of the Regional Development Work Plan in the Planning and Budgeting Process of Bekasi City - Indrijantoro, Widodo; Irwansyah, Iwan; Fahriyah, Aramia (PT FORMOSA CENDEKIA GLOBAL, 2024)
Based on the Bekas City RPJPD 2005 – 2025 and 2020 – 2024 RPJMD, the Bekas City Government has prepared the 2023 Bekas City RKPD based on the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 17 of 2021 concerning Guidelines for Preparing Regional Government Work Plans for 2022 because it has not been implemented. There is a new Minister of Home Affairs Regulation regarding Guidelines for Preparing Regional Government Work Plans for 2023.In this research, the author used a descriptive qualitative approach. The Regional Development Work Plan (RKPD) is a very important tool in the planning and budgeting process, as a description of annual programs and activities as the basis for General Budget Policy and Temporary Budget Ceiling Priorities. The RKPD must be reviewed by the Bekasi Inspectorate, to ensure quality there is harmony between the RPJMD and RKPD, so that the development stages per year are in accordance with those that have been determined. The review issues recommendations as a quality assurance function that must be followed up, and after the review is carried out, a Mayor's Regulation regarding RKPD is stipulated. In discussing the RAPBD, it must be based on the RKPD, and adjustments can be made to the budget ceiling for each program and activity.